The Center-of-Government: Lessons form the Chilean Experience During the Governments of the Concertación (1990 - 2010) - Egaña Baraona, Rodrigo; Chateau Herrera, Jorge (Estado, Gobierno y Gestión Pública, 2011)
The paper analyzes how the OECD’s concept of Center-of-Government has been applied in Chile during the governments of the Concertación of Parties for Democracy (1990-2010). The various functions of the Centre-of-Government are presented and the ways in which each was organized and executed during each of the four governments is analyzed. A set of conclusions derived from the Chilean experience is proposed and which may be useful for the organization of the Centre-of-Government in countries that have political, economical and social similarities with Chile.